Does it pay to be active? - Piotrowska, Sylwia; Majchrzycki, Marian; Rogala, Piotr; Gołębiewski, Patryk (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. During their career athletes are at risk of injuries due to high-intensity training, overtraining, and untreated sports-related micro-injuries. As they advance in years, they experience the results of previous injuries. Aim of Study. The aim of the study was to evaluate the effects of physical activity and their changes on the quality of life in the old age. Material and Methods. A review of literature was performed with the use of keywords: “sport injuries”, “aging”, “quality of life”, “old age”, “former athletes”, “osteoarthritis”, “physical activity” in databases such as PubMed, SPORTDiscus, MEDLINE, Springer, Google Scholar. Results. Degenerative changes in the joints are far more common in former athletes than in the general population. Well-developed muscles resulting from sustained physical activity prevent limitations in daily life (including those resulting from degenerative changes). Degenerative changes caused by long-time sport activity have no significant effect on the quality of life in older people. Conclusion. Physical activity plays an important role in reducing physical deficits in everyday life of the elderly, thus contributing to improving their quality of life
Keywords: physical activity; injuries; old age; osteoarthritis; quality of life